AB0275 14-3-3 eta is an independent marker of joint damage that complements CRP and anti-CCP. (23rd January 2014) - van der Heijde, D.; Landewé, R.; Allaart, C.F.; Tak, P.P.; Marotta, A.; Maksymowych, W.P.
Abstract : Background: Rheumatoid arthritis (RA) is a progressive multi-factorial disease that if left untreated can lead to severe disability in approximately 20 - 30% of patients. To improve outcomes, an early definitive diagnosis, estimating the relative risk of developing erosive irreversible disease together with proposing an optimal treatment strategy is essential. We have previously reported that serum 14-3-3η is a highly specific marker of RA, combines with RF and anti-CCP to improve diagnosis in both early and established disease, and behaves as an extracellular ligand activating factors involved in joint degradation (MMPs and RANKL). Levels of this marker in both synovial fluid and serum significantly correlate with levels of MMP-1 and MMP-3 further characterizing 14-3-3η's involvement in the joint damage process. Objectives: To investigate the association between serum 14-3-3η expression and joint damage in RA. Methods: To evaluate 14-3-3η's expression in RA patients with and without joint damage, the serum of 50 patients from the year-three time-point of the BeSt (Behandel-Strategieën) study were measured using an investigational-grade 14-3-3η ELISA. There were 35 patients with joint damage (SHS ≥0.5) and 15 age and DAS-matched patients with no joint damage (SHS <0.5). Two-tailed t-tests were run to compare group differences. Pearson correlations were generated to determine relationships between 14-3-3η, RF, anti-CCP or CRP. Regression analyses were performed to identify which variables were independently associated with and which combined best to mark joint damage. Results: Mean 14-3-3η serum concentrations were statistically significantly higher in patients with joint damage when compared to those without; 5.23 versus 1.31ng/ml, respectively (p=0.048). Across the entire cohort, 14-3-3η did not correlate with titres of either RF (r=0.18), anti-CCP (r=0.07) or CRP (r=-0.08) underscoring its independence of these serum markers. As shown in the table below, titres of CRP, anti-CCP, 14-3-3η were indicative of joint damage status. RF positivity too was indicative of joint damage although the model was not strengthened by combining it with any of the serological markers. Adding 14-3-3η to CRP and anti-CCP significantly improved the association of these markers with joint damage as shown below. CRP with anti-CCP delivered an ROC AUC of 0.80 (Chi-Sq =11.7) whereas when combined with 14-3-3η the ROC AUC increased to 0.85 (Chi-Sq =15.3). Conclusions: Serum 14-3-3η expression is independent of other RA serological markers and when used in combination with CRP and anti-CCP serves as a disease-specific biomarker to independently inform the joint damage process. Disclosure of Interest: D. van der Heijde: None Declared, R. Landewé: None Declared, C. Allaart: None Declared, P. Tak: None Declared, A. Marotta Shareholder of: Co-founder, W. Maksymowych: None Declared